(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
This research, “The Consequences of the First World War on Germany”, is an attempt to shed the light on the most significant influences of the World War (1) on Germany including the political, economic, military, and social domains. The importance of this research comes from the need for a study in Arabic within the same area. In addition the research proves that the biggest loser in wars are the countries whose lands were the battlefields of the war such as the Arab countries today. Furthermore, the scientific historical analytical approach was adopted through collecting data and making a comparison and analysis out of them. Moreover, Germany suffered many hardships from the First World War. However, it was strong enough to recover and develop rapidly in all domains especially in the liberation of women.